Growth Factors in the Platelet-Rich Plasma - Gonzalez, Maczy; Arteaga-Vizcaino, Melvis; Ruiz, Ana; Estevez, Jesus; Quintero, Jesus; Quintero, Maribel; Briceño, Olga; Atencio, Ricardo; Marcano, Ivis (Journal of Hematology Research, 2017)
PRP is an useful bioproduct to tisular regeneration. The aim of study was evaluate the concentration of growth factors: PDGFBB (platelet-derived growth factor), EGF(epidermal growth factor) and VEGF (vascular endothelial growth factor) present in the Platelet-rich plasma (PRP) in subjects treated with drugs which inhibit platelet aggregation as acetylsalicylic acid (ASA) and clopidogrel before and after administration. We determined by ELISA PDGFBB, EGF and VEGF levels in PRP, Platelet Poor Plasma (PPP), lysate and exudate from 32 healthy subjects before and 24 hours after ingesting acid Acetyl salicylic acid (ASA) and clopidogrel as a single dose. The PRP and PPP were obtained by the method of Anitua by single centrifugation method. To analyze the results of student test and Pearson correlation was applied, with statistical significance level of p < 0.05. PPP and exudate (Clopidogrel: p < 0.001), PRP (Clopidogrel: p < 0.01) statistically significant differences for PDGFBB in PPP (p < 0.01 AAS) were found, and for VEGF in lysate (ASA and Clopidogrel: p < 0.05). No significant difference was found for EGF. Only was no correlation between baseline values of EGF in the ASA group and the respective PRP platelet count (r = 0.726). The results show that the average basal values of the three growth factors measured were considered particularly high in the PRP and lysate, showing the significant decrease for PDGFBB after antiplatelet therapy, especially of Clopidogrel and a significant increase for the VEGF only for the lysate. Although the behavior of three different soluble mediators was different to antiplatelet agents, the observed changes support the conclusion that a single dose of these drugs not markedly affect the secretion and availability of the three growth factors measured in various platelet derived obtained.